2016
DOI: 10.3390/molecules21101350
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Plant Extracts of Erythroxylum sp. against Toxic Effects Induced by the Venom of Lachesis muta Snake

Abstract: Snake venoms are composed of a complex mixture of active proteins that induce toxic effects, such as edema, hemorrhage, and death. Lachesis muta has the highest lethality indices in Brazil. In most cases, antivenom fails to neutralize local effects, leading to disabilities in victims. Thus, alternative treatments are under investigation, and plant extracts are promising candidates. The objective of this work was to investigate the ability of crude extracts, fractions, or isolated products of Erythroxylum ovali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…5 ; Table 5 ). Besides, recent studies reported five triterpenes ( 92–96 ) from E. ovalifolium [ 14 ], E. daphnites [ 48 ] or E. macrocalyx [ 49 ]. Interestingly, all the triterpenoids identified in this genus are pentacyclic triterpenes.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 ; Table 5 ). Besides, recent studies reported five triterpenes ( 92–96 ) from E. ovalifolium [ 14 ], E. daphnites [ 48 ] or E. macrocalyx [ 49 ]. Interestingly, all the triterpenoids identified in this genus are pentacyclic triterpenes.…”
Section: Chemical Compositionmentioning
confidence: 99%
“… Compounds name Plant source Refs. 108 ombuin E. nummularia [ 44 ] 109 ombuin-3- O -rutinoside E. alaternifolium , E. campestre , E. barbatum , E. argentinum , E. tenue , E. daphnites , E. loefgrenii , E. engleri , E. cuneifolium , E. lucidum , E. pruinosum , E. pulchrum , E. squamatum , E. subracemosum , E. subrotundum , E. vacciniifolium , E. novogranatense [ 59 , 66 – 71 ] 110 ombuin-3- O -rutinoside-5- O -glucoside E. argentinum , E. cuneifolium , E. pulchrum , E. macrocalyx [ 49 , 67 , 70 , 71 ] 111 quercetin E. rimosum , E. lucidum , E. suberosum , E. ovalifolium [ 14 , 46 , 59 ] 112 quercetin-3- O -rutinoside E. argentinum , E. cambodianum , E. alaternifolium , E. engleri , E. loefgrenii , E. leal - costae , E. lucidum , E. pruinosum ...…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with other species in the genus, E. ovalifolium can produce tropane alkaloids. Medicinal triterpenoids, such as friedelin ( 6 ) and lupeol ( 7 ) Figure 4, and a host of flavonoids have also been detected in E. ovalifolium extracts [61].…”
Section: An Overview Of Bioprospection and Pharmacological Researcmentioning
confidence: 99%
“…The triterpenoids friedelin ( 6 ) and lupeol ( 7 ) isolated and described in E. ovalifolium extracts [61]. …”
Section: Figurementioning
confidence: 99%